Examining the antecedents and consequences of gratitude. Issue 1 (13th February 2017) - Fazal E. Hasan, Syed; Mortimer, Gary; Lings, Ian N.; Neale, Larry
Abstract : Purpose: This study aims to propose the emotional response of gratitude as a mediating mechanism to explain the relationship between perceptions of a service organisations' relationship marketing investments, customer cynicism and reciprocity and overall satisfaction. Further, the study seeks to test the significance of the mediation effects of these constructs on customer overall satisfaction. Design/methodology/approach: Using theories from service marketing and consumer psychology, this study develops and tests a customer gratitude model (CGM). Field surveys based on existing measures were used to elicit data from 1, 104 respondents. The measures were validated and subsequently the CGM was tested to establish the veracity if the nomological network presented. Findings: Results indicate that perceived relationship marketing investment exerted an indirect effect on gratitude through the mediating effect of reciprocity and cynicism. Further, perceived relationship marketing investments impacted overall satisfaction through its mediating effect of gratitude, and gratitude explained the indirect influences of reciprocity and customer cynicism on overall satisfaction. Research limitations/implications: This study contributes to services marketing literature by examining the emergent role of gratitude between customer perceptions of service organisations and pro-organisational attitudes, like overall satisfaction. Practical implications: This research encourages service organisations to implement relationship-building strategies, beyond that of purely economic benefits, that seek to enhance the emotion of gratitude, which will lead to greater overall customer satisfaction. Originality/value: Despite emphasising relationship longevity between customers and service organisations, literature has not yet focused on the role of gratitude. The CGM provides valuable insights for further inquiries.